Peningkatan Pengetahuan Pada Perawat Dan Kader Kesehatan Di Puskesmas Wilayah Kota Cimahi Melalui Pelatihan Terapi Pijat Akupresur - Sri Wulandari Novianti; Suharjiman; Rini Mulyati; Lina Safarina; Ismafiaty; Chatarina Suryaningsih; M. Budi Santoso; Yuswandi; Hikmat Rudyana; Hemi Fitriani; Juju Juhaeriah (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
Health problems in Indonesian society are still a challenge to control. In addition to infectious diseases, non-communicable diseases still have a high number in the community. Efforts to improve and maintain health in the community are carried out through medical therapy and complementary traditional therapies. One of the complementary therapies that have been widely researched and safe to do is acupressure massage therapy. Several studies have proven the effectiveness of acupressure massage therapy in overcoming health problems in body system disorders. The S1 Nursing Study Program and the Nursing Profession of FITKES UNJANI in its curriculum include acupressure complementary nursing. As an application and contribution in overcoming health problems in the community, community service is carried out in collaboration with Public Health Centers throughout the Cimahi City Region to increase knowledge about acupressure massage for Nurses and Health Cadres. The results of this community service show there is a significant influence in increasing the knowledge of Nurses and Health Cadres after being given material about acupressure massage therapy. Keywords: Knowledge, Nurses and Health Cadres, Acupressure Massage